Stedman's medical dictionary : - Stedman, Thomas Lathrop (Williams & Wilkins, 1995)
This medical reference contains over 100,000 entries. This edition features: 12,000 new terms; 125 high-profile terms with expanded definitions; English translations of Latin terms; 29 anatomical charts; subentries; and a word-finder.